2018
DOI: 10.1177/1087724x18757535
|View full text |Cite
|
Sign up to set email alerts
|

Pavement Condition and Residential Property Values: A Spatial Hedonic Price Model for Solano County, California

Abstract: Transportation agencies invest billions of dollars every year in resurfacing roadways, ostensibly to improve the travel experience. When locally funded, one justification for increased expenditure on the pavement surface is that it could increase property values. We evaluated this approach directly, using hedonic regression to estimate the relationship between pavement condition and residential property value in Solano County, California. We hypothesized that improving pavement condition would positively affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…Figure 10 shows the increase in in-vehicle vibration for the test cases, due to active DRTRS. Similar to invehicle noise, the results varied with speed and vehicle type, but were consistently above the upper ceiling of detectable vibration of 4.25 ms 22 . The only exception was in-vehicle at 40 mph in the case of the diesel truck, which might be explained by the larger tire size and nature of the vehicle's suspension absorbing more vibrations.…”
Section: In-vehicle Noise and Vibrationmentioning
confidence: 65%
See 1 more Smart Citation
“…Figure 10 shows the increase in in-vehicle vibration for the test cases, due to active DRTRS. Similar to invehicle noise, the results varied with speed and vehicle type, but were consistently above the upper ceiling of detectable vibration of 4.25 ms 22 . The only exception was in-vehicle at 40 mph in the case of the diesel truck, which might be explained by the larger tire size and nature of the vehicle's suspension absorbing more vibrations.…”
Section: In-vehicle Noise and Vibrationmentioning
confidence: 65%
“…One study indicated that an increase in the sound level, from the ambient noise level, by 4 dB is detectable, 15 while another study indicated that 7 dB is detectable. 16 Other studies have demonstrated that TRS can generate an extra 10-17 dB of in-vehicle noise 14,17 and up to 2.55 ms 22 of vibration, 18 compared with those produced only by ambient roadway conditions. This extra noise and vibration has been found sufficient to alert drivers.…”
Section: Noise and Vibration For Inattentive Driversmentioning
confidence: 98%
“…Landfills and delinquency . Seo, Salon, Shilling and Kuby (2018). Contaminated land, irreversible and irreparable damage to nature Horváth and Hajnal (2014); Chen and Li (2017); Taylor, Phaneuf and Liu (2016).…”
Section: Negative Externalitymentioning
confidence: 99%
“…Landfill of debris Seo, Salon, Shilling and Kuby (2018). Presence of a nearby landfill Jauregui and Hite (2005); Chen and Li (2017).…”
Section: Negative Externalitymentioning
confidence: 99%
“…Một số nghiên cứu xem xét mối quan hệ giữa cõ sở hạ tầng, thiết kế của đường xá và giá trị bất động sản (Fullerton & Villalobos, 2011;Gonzalez-Navarro & Quintana-Domeque, 2010;Seo, Salon, Shilling, & Kuby, 2018). Sử dụng mô hình hồi quy OLS và mô hình với biến công cụ (IV) ứng dụng với giá giao dịch nhà ở riêng lẻ thực tế tại Mexico trong giai đoạn 2006 -2010, kết quả nghiên cứu cho thấy bề mặt đường bằng phẳng sẽ làm tăng giá trị nhà ở riêng lẻ từ 21 đến 25% (Gonzalez-Navarro & Quintana-Domeque, 2010).…”
Section: Nghiên Cứu Thực Nghiệmunclassified